Prevalence and Impact of Cerebrovascular Risk Factors in Patients with Giant Cell Arteritis: An Observational Study from the Spanish National Registry - Sánchez-Chica, Enrique; Martinez-Urbistondo, María; Rojas, Ángela Gutierrez; Castejón, Raquel; Mellor-Pita, Susana; Campo, Pedro Durán-del; Tutor-Ureta, Pablo; Vargas-Núñez, Juan A; Moreno-Torres, Víctor (Cardiology and Cardiovascular Medicine, 2022)
Objectives: To assess the prevalence and impact of cerebrovascular risk factors (CRF) on major cerebrovascular events in patients with Giant Cell Arteritis (GCA). Methods: Analysis of the patients diagnosed with GCA identified in the Spanish Hospital Discharge Database between 2016 and 2018. Admissions due to cerebrovascular events (CVE, composed by stroke and transient ischemic attack) were compared to the admissions due to other causes. The factors related to cerebrovascular events were assessed by a multivariate logistic regression analysis. Results: 8,474 hospital admissions from patients diagnosed with GCA were identified. Mean age was 80.8 years and 36.4% were male. 67.2% were hypertense, 27.8% diabetic, 36.7% dyslipidemic, 14.2% smokers and 6.8% presented prior atherosclerosis diagnosis. Overall mortality rate was 6.5%. 3.4% of the admissions were motivated by CVE (stroke in 2.8% and TIA in 0.6%). When compared with admissions due to other causes, the patients who suffered from CVE presented a higher rate of male sex (36.2 vs 43.5 %, p=0.007), hypertension (66.9% vs 74.4%, p=0.004), diabetes (27.6% vs 33.7%, p=0.016) and atherosclerosis (6.6% vs 10.2%, p=0.0017). After adjustment, male sex (OR= 1.35, 95% CI 1.06-1.72) and mainly hypertension (OR=1.44, 95% CI 1.11-1.90) were associated with a higher risk of CVE. Conclusion: Hypertension, along with male sex, was the strongest risk factor for cerebrovascular events in GCA patients. In these high-risk patients, antiplatelet therapy should be re-considered and evaluated in prospective studies.